Analisis Risiko Keselamatan dan Kesehatan Kerja pada Aktivitas Operasional Gudang Sortir Menggunakan Metode HIRADC - Danisarah Prilly; Yatna Suhetna; Mirza Nafaru Haqa (KOLONI, 2026)
The rapid growth of the logistics and warehousing sector, particularly in sorting operations, has increased job complexity involving manual handling, repetitive movements, and operational pressure due to high distribution volumes. These conditions potentially elevate occupational safety risks and musculoskeletal disorders if not managed through a systematic occupational health and safety (OHS) risk management approach. This study aims to identify potential hazards and analyze risk levels in parcel sorting activities in a sorting warehouse using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. A qualitative descriptive approach was applied through direct observation, interviews, and documentation across several sorting warehouses in Tangerang, Indonesia. Job Hazard Analysis (JHA) was used to decompose work activities, followed by risk assessment based on likelihood and severity to determine risk levels and control recommendations. The results indicate that most activities fall under moderate risk, while loading activities into distribution vehicles represent the highest risk category. The dominant hazards are related to manual handling, repetitive movements, interaction with equipment, and inadequate housekeeping conditions. In addition, existing controls were found to be inconsistently implemented, reducing their effectiveness. This study concludes that the HIRADC approach provides a systematic overview of hazards and risk levels in sorting warehouse operations, serving as a basis for prioritizing more effective and context-based OHS control measures in the logistics sector.